Inhibition of Streptococcus mutans biofilm formation on composite resins containing ursolic acid - Soohyeon Kim; Minju Song; Byoung-Duck Roh; Sung-Ho Park; Jeong-Won Park (Korean Academy of Conservative Dentistry, 2013)
Objectives To evaluate the inhibitory effect of ursolic acid (UA)-containing composites on Streptococcus mutans (S. mutans) biofilm. Materials and Methods Composite resins with five different concentrations (0.04, 0.1, 0.2, 0.5, and 1.0 wt%) of UA (U6753, Sigma Aldrich) were prepared, and their flexural strengths were measured according to ISO 4049. To evaluate the effect of carbohydrate source on biofilm formation, either glucose or sucrose was used as a nutrient source, and to investigate the effect of saliva treatment, the specimen were treated with either unstimulated whole saliva or phosphate-buffered saline (PBS). For biofilm assay, composite disks were transferred to S. mutans suspension and incubated for 24 hr. Afterwards, the specimens were rinsed with PBS and sonicated. The colony forming units (CFU) of the disrupted biofilm cultures were enumerated. For growth inhibition test, the composites were placed on a polystyrene well cluster, and S. mutans suspension was inoculated. The optical density at 600 nm (OD600) was recorded by Infinite F200 pro apparatus (TECAN). One-way ANOVA and two-way ANOVA followed by Bonferroni correction were used for the data analyses. Results The flexural strength values did not show significant difference at any concentration (p > 0.01). In biofilm assay, the CFU score decreased as the concentration of UA increased. The influence of saliva pretreatment was conflicting. The sucrose groups exhibited higher CFU score than glucose group (p < 0.05). In bacterial growth inhibition test, all experimental groups containing UA resulted in complete inhibition. Conclusions Within the limitations of the experiments, UA included in the composite showed inhibitory effect on S. mutans biofilm formation and growth.